2001
DOI: 10.1258/0956462011916848
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities and plasmid patterns of Neisseria gonorrhoeae in Bénin

Abstract: This study describes antimicrobial susceptibility patterns of Neisseria gonorrhoeae isolates obtained from female sex workers in Cotonou, Bénin. All isolates were susceptible to spectinomycin, ceftriaxone and ciprofloxacin, and susceptible to moderately susceptible to kanamycin; 9.8% of isolates were resistant to thiamphenicol; 9%, 87.5% and 3.5% were susceptible, moderately susceptible, resistant to trimethoprim-sulfamethoxazole, respectively; 94.4% and 99.3% were resistant to penicillin and tetracycline, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, when exposed in Asia, 63% of the N. gonorrhoeae isolates studied in paper III were not fully susceptible to ciprofloxacin, compared with 7% when exposed somewhere else. When exposed in Africa, all cases were susceptible to ciprofloxacin which is in concordance with other studies and may reflect that this drug is not commonly used in this part of the world [105]. From a microbiologic point of view, it would be advisable to use another drug as the first drug of choice, if the patient is exposed in Asia, before antibiotic susceptibility pattern is analysed.…”
Section: Antimicrobial Susceptibility and Choice Of Treatmentsupporting
confidence: 86%
“…However, when exposed in Asia, 63% of the N. gonorrhoeae isolates studied in paper III were not fully susceptible to ciprofloxacin, compared with 7% when exposed somewhere else. When exposed in Africa, all cases were susceptible to ciprofloxacin which is in concordance with other studies and may reflect that this drug is not commonly used in this part of the world [105]. From a microbiologic point of view, it would be advisable to use another drug as the first drug of choice, if the patient is exposed in Asia, before antibiotic susceptibility pattern is analysed.…”
Section: Antimicrobial Susceptibility and Choice Of Treatmentsupporting
confidence: 86%
“…The latest guidelines from WHO recommend a dual therapy combining ceftriaxone or cefixime plus azithromycin in settings where local resistance data are not available 2. The results from this study are online with these recommendations but suggest that dual therapy may not be necessary.…”
mentioning
confidence: 55%
“…In sub-Saharan Africa, where the syndromic approach and empirical antibiotic therapy, as promoted by the WHO, are largely used, information available on antimicrobial susceptibility of Neisseria gonorrhoeae is scarce 1. To our knowledge, the last study on antimicrobial susceptibility of N. gonorrhoeae in Benin was performed in 1999–2000 and found that all isolates were susceptible to ceftriaxone and ciprofloxacin 2. The present study was undertaken to update this information and to enhance global surveillance by the WHO.…”
mentioning
confidence: 94%
“…However, kanamycin has rarely been used for gonorrhoea treatment in other countries, no randomised controlled clinical trials have been performed, appropriate pharmacokinetic/pharmacodynamic data for the treatment of urogenital and extragenital gonorrhoea are lacking and quality-assured data regarding clinical efficacy are exceedingly limited, and mainly lacking for women and in extragenital gonococcal infections. Furthermore, despite that the in vitro resistance to kanamycin is rarely examined internationally, resistance and intermediate resistance to kanamycin have been described from many regions worldwide, for example, in Russia,26 Armenia,27 Indonesia,28 Benin,29Mozambique,30 which is one of the neighbouring countries to Zimbabwe, and also previously in Zimbabwe in the 1990s 31. Nevertheless, the in vitro resistance to kanamycin in Zimbabwe appears to have remained relatively low despite its use for the treatment of gonorrhoea for several decades and additional infections such as multidrug-resistant tuberculosis.…”
Section: Discussionmentioning
confidence: 99%